SOLVENCY II TECHNICAL PROVISIONS FOR GENERAL INSURERS. (6th February 2015) - Dreksler, S.; Allen, C.; Akoh-Arrey, A.; Courchene, J. A.; Junaid, B.; Kirk, J.; Lowe, W.; O'Dea, S.; Piper, J.; Shah, M.; Shaw, G.; Storman, D.; et al.
Abstract This paper brings together the work of the GI Solvency II Technical Provisions working party. The working party was formed in 2009 for the primary purpose of raising awareness of Solvency II and the impact it would have on the work that reserving actuaries do. Over the years, the working party's focus has shifted to exploring and promoting discussion of the many practical issues raised by the requirements and to promoting best practice. To this end, we have developed, presented and discussed many of the ideas contained in this paper at events and forums. However, the size of the subject means that at no one event have we managed to cover all of the areas that the reserving actuary needs to be aware of. This paper brings together our thinking in one place for the first time. We hope experienced practitioners will find it thought provoking, and a useful reference tool. For new practitioners, we hope it helps to get you up-to-speed quickly. Good luck!